Availability of Primary Nutrients and Physicochemical Properties of Soil as Influenced by Integrated Nutrient Management on Typic Heplustept of Rajasthan - Kiran Doodhwal, Sushila Aechra and Jitendra Kumar Sharma, Abhitej Singh Shekhawat, H.S. Purohit, Gajanand Jat, Jitendra Singh Bamboriya (Journal of the Indian Society of Soil Science, 2022)
A two-year study was conducted on the instructional farm of Rajasthan College of Agriculture, Udaipur during kharif 2018 and kharif 2019. The objective of this study was to investigate the effect of integrated nutrient management on different physical and chemical properties of the soil. The results of the study show a superiority of integrated nutrient management over sole application of chemical fertilizers in terms of physicochemical properties of the soil. The integrated combinations gave the best results significantly as compared to control and sole application of chemical fertilizers in terms of bulk density (1.32 Mg m-3), porosity (48.9%), water holding capacity (47.9%), infiltration rate (0.924 cm h-1), soil aggregates (61.2%), electrical conductivity (0.81 dS m-1), cation exchange capacity [12.9 cmol(p+)kg-1], soil organic carbon (0.79%), total organic carbon (1.25%), available N (421 kg ha-1), P (28.95 kg ha-1) and K (615 kg ha-1) in soil and their uptake by maize.